Development of Spiritual Tourism of Penglukatan at Tirta Empul Temple as A Balinese Cultural Heritage - Kadek Aditya Prasetya Putra; Nyoman Diah Utari Dewi; Ni Putu Tirka Widanti (Pengurus Pusat Perkumpulan Ilmuwan Administrasi Negara Indonesia (PIANI), 2026)
Abstract Spiritual purification tourism (melukat) at Tirta Empul Temple has expanded rapidly, strengthening local livelihoods while generating overtourism pressures that threaten ritual sacredness, customary space, and environmental carrying capacity. This study aims to describe preservation dynamics, economic effects, and visitor-governance challenges, and to derive policy-relevant recommendations. Theoretical framing draws on spiritual–cultural tourism, the Tri Hita Karana value system, and destination governance and carrying-capacity perspectives. A descriptive qualitative design was employed, combining two weeks of participant observation, semi-structured in-depth interviews with 15 purposively selected key informants, and document analysis of regional regulations and levy records. Data were analysed iteratively using Miles and Huberman’s procedures (reduction, display, conclusion drawing), supported by source/method triangulation and member checking. Findings indicate a trade-off between ritual authenticity and market-driven commodification, alongside SMEs’ dependence on visitor flows. The study proposes a zoning framework and SWOT-based strategy, including time-slot digital quotas, strengthened ritual etiquette SOPs, and conservation-oriented revenue allocation. Keywords: Tirta Empul Temple, Tri Hita Karana, Overtourism